Idiopathic Chronic Eosinophilic Pneumonia: Retrospective Analysis of 17 Cases from a Single Center in Turkey - (:unkn) unknown (AVES, 2016)
Objective: Idiopathic chronic eosinophilic pneumonia (ICEP) is a rare eosinophilic lung disorder with an unknown etiology and is characterized by subacute or chronic respiratory and general symptoms, alveolar and/or peripheral eosinophilia, and the accumulation of eosinophils in the lungs. We aimed to present diagnostic test results and follow-up outcomes of 17 patients who were diagnosed with ICEP in our hospital in light of literature. Methods: Between 2008 and 2013, we examined 17 cases of ICEP. We evaluated clinical and laboratory findings together with the long-term follow-up data. Results: The patients had a mean age of 40.8 years at presentation, and the female/male ratio was 0.8. The most common symptoms were cough (94%), shortness of breath (76%), and high fever (35%). Bronchoalveolar lavage eosinophil percentages of the patients ranged from 3% to 80%. Nine (53%) patients experienced recurrence. Six patients were maintained on low dose steroid due to repeating relapses. Among these patients, 7 (77.7%) had a total IgE level of above 500/IU/mL. Conclusion: Relapses are common in ICEP after the withdrawal of corticosteroid treatment or during dose reduction. We point out the importance of the close monitoring of patients for identifying relapse. A higher total IgE level during diagnosis may serve as a predictor of recurrence.
Keywords: Corticosteroid; eosinophil; recurrence; total IgE; TERM-FOLLOW-UP; PULMONARY-EDEMA